INOVASI PRODUK LEKER DARI TEPUNG LABU KUNING DENGAN ISIAN PURE PUMPKIN DAN PURE UBI UNGU - Okta Dzakwan Permadi; Tito Pandu Raharjo (Media Bina Ilmiah, 2024)
This research aims to make leker products that use pumpkin flour as the main ingredient, produced by drying and grinding pumpkin flesh. Leker products made through organoleptic tests have satisfactory production value and offer various flavors. This experimental research uses pumpkin flour to substitute wheat flour in leker products. The main objective of this research is to find the right recipe formula and determine how well customers accept it by administering an organoleptic test questionnaire to fifty respondents. Consumers are tested for taste, color, aroma, texture, appearance, and acceptability. The results of this research show that the recipe formula using pumpkin flour as a substitute for wheat flour in the leker dough gave quite good results. Additionally, the organoleptic test results, gathered from distributing questionnaires to 50 panelists randomly, showed average scores of 4 and 5. From this assessment, it can be concluded that the pumpkin flour leker product as a substitute for wheat flour can be accepted by consumers